O Prêmio Escola Nota Dez e suas implicações à subjetividade das crianças do 2º do ensino fundamental do estado do Ceará - Araújo, Karlane Holanda (2020)
This study aimed to analyze the effects of the school accountability policy represented by the Escola Nota Dez Prize produced on the subjectivity of 2nd grade children of Elementary School in the state of Ceará. For this version of the survey, the repercussions of this event were mapped in five municipalities distributed in the Regional Coordination of Education Development [Coordenadorias Regionais de Desenvolvimento da Educação], located in the hubs: north (Regional Coordination 3 - Morrinhos), south (Regional Coordination 18 - Nova Olinda), east (Regional Coordination 10 - Fortim), west (Regional Coordination 13 - Novo Oriente) and center (Regional Coordination 12 - Quixeramobim) of Ceará. In each of these coordination, the municipalities that obtained the highest number of schools awarded the Escola Nota Dez Prize in 2014 and 2015 were selected. Subsequently, the schools with the best performances in each of these cities were extracted. For data collection, the technique of semi-structured interview with 2nd grade polyvalent teachers was applied, as well as the group interview with the children of the researched series. Due to the qualitative nature of this study, the lines of research participants were analyzed based on Gadamerian hermeneutics, especially with the application of the horizons fusion notion. At the end of the survey, it was possible to see that the culture of productivity and recognition of the merit of the school accountability policy, represented by Escola Nota Dez Prize, reverberates in the educational action, so that the school and its staff, throughout the school year, undertake efforts (reward sermon and aversive controls) in order to instruct the student to achieve the performance of excellence (standard student) stated in the Spaece-Alfa descriptors and, by effect, be recognized and awarded with the money. In this perspective, the child who is in the process of formation and constitution of his subjectivity and identity is reduced to the position of passive “object”, stimulated to accomodate himself to the teaching-learning process and pressured to respond to the demand of “school effectiveness”. In this sense, the Escola Nota Dez Prize reinforces pedagogical practices in the light of the capital logic, which are socially valued, producing effects in the subjectivation of values, conducts and social bonds of the children from elementary schools with high performance (2nd grade) of Ceará state. Faced with this finding, we consider that the formation of our students will not improve if we continue to focus only on reading, math, and tests as a means of deciding the fate of students, teachers, principals and schools, while we ignore other studies that are essential elements of a good education. It is necessary to break the circuit of marketing longings, for that it is urgent the meta-evaluation of the program and the adoption of a new educational policy proposal that prioritizes the humanistic values constituted in the social relations within the school environment, as well as the child integral development.